Take the 2-minute tour ×
Physics Stack Exchange is a question and answer site for active researchers, academics and students of physics. It's 100% free, no registration required.

In the following demonstration, there is an error, but I cannot find where. (I explicitely put the $c^2$ to keep track of units).

We consider a metric $g_{\mu\nu}$ with a signature $(-, +, +, +)$ :

$\boxed{g_{\mu\nu} = \begin{pmatrix} -c^2 & 0 & 0 & 0 \\ 0 & 1 & 0 & 0 \\ 0 & 0 & 1 & 0 \\ 0 & 0 & 0 & 1 \end{pmatrix}} \qquad\qquad \boxed{ g^{\mu\nu} = \begin{pmatrix} \frac{-1}{c^2} & 0 & 0 & 0 \\ 0 & 1 & 0 & 0 \\ 0 & 0 & 1 & 0 \\ 0 & 0 & 0 & 1 \end{pmatrix}} $

The tensor of a perfect fluid is: $ \boxed { \begin{aligned} T^{\mu\nu} &= \left(\rho c^2+P\right)u^{\mu}u^{\nu}+Pg^{\mu\nu}\\ T_{\nu}^{\mu} &= \left(\rho c^2+P\right)u^{\mu}u_{\nu}+P\delta_{\nu}^{\mu}\\ T_{\mu\nu} &= \left(\rho c^2+P\right)u_{\mu}u_{\nu}+Pg_{\mu\nu} \end{aligned} }$ where $\rho$ is the mass density.

We can easily check that $\rho c^2$ and $P$ have the same unit.

If we consider only the first component $00$, there is no pressure $P$ involved (I consider a cosmological case where the fluid is at rest in comoving coordinates). The only solution to have that is that $u^0u^0=-g^{00}$, so that the contravariant perfect fluid tensor become : $T^{00} = \left(\rho c^2+P\right)u^{0}u^{0}+Pg^{00}=\left(\rho c^2+P\right)\times{-g^{00}}+Pg^{00}=-\rho c^2 g^{00} = -\rho c^2 \times -\frac{1}{c^2}=\rho$ which is the expected result. So, to have the expected result, one should have $\boxed{\left(u^0\right)^2=+\frac{1}{c^2}}$.

Now come the weird part.

The metric can be written: $ds^2=g_{\mu\nu}dx^{\mu}dx^{\nu}=-c^2dt^2+dx^2+dy^2+dz^2=dt^2\left(-c^2+\frac{dx^2}{dt^2}+\frac{dy^2}{dt^2}+\frac{dz^2}{dt^2}\right)\approx-c^2dt^2$ which is equivalent to :

$\frac{dt^2}{ds^2}\approx-\frac{1}{c^2}$

which means : $\boxed{\left(u^0\right)^2=-\frac{1}{c^2}}$

So we clearly have a problem of sign here between the two expressions of $u^0$.

QUESTION: where is the mistake ?

share|improve this question
    
$u^0 = \gamma c$, and not just $-g_{00}$, you don't cancel the pressure part on the calculation of $T^{00}$ –  Hydro Guy May 5 '13 at 14:01
    
If I consider a fluid at rest in comoving coordinates, then I think that $T^{00}=\rho$ –  Vincent May 5 '13 at 14:11
    
Even so, you can't do the reasoning that you are doing on the second part. You have $u^\mu=c\frac{dx^\mu}{ds}$, and you can't really set '$dx^2=dy^2=dz^2=0$ –  Hydro Guy May 5 '13 at 14:23
    
In the second part, as my fluid is at rest, I think that the terms $\frac{dx}{dt}$, $\frac{dy}{dt}$, $\frac{dz}{dt}$ are negligible compared to $c^2$, isn't it ? –  Vincent May 5 '13 at 14:31
    
I'm reviewing my calculations, and here's why I hate the $g_{\mu\nu}=diag(-1,1,1,1)$: you define $u^{\mu} = - c\frac{dx^\mu}{ds}$ because you have for time-like intervals in this signature $cd\tau = -ds$ and you always have $u^\mu=\frac{dx^\mu}{d\tau}$, and there you have your sign problem. –  Hydro Guy May 5 '13 at 14:41

1 Answer 1

up vote 3 down vote accepted

A perfect fluid is defined by the property that, in the local rest frame, it allows no energy fluxes and no anisotropic stresses. Thus, at a given space-time point, in the local rest frame [in which the components of the 4-velocity are $u^{\alpha} = (1, 0, 0, 0)^{\mathsf{T}}$], the energy momentum tensor components are $T^{\alpha\beta} = \mathrm{diag}(e, p, p, p)$ where $e$ is the local energy density, $p$ is the pressure in the local rest frame. So in general coordinates, the form of the energy-momentum tensor (as you have written) is

$$T^{\alpha\beta} = (e + p)u^{\alpha}u^{\beta} + pg^{\alpha\beta}.$$

Assuming units where $c = 1$. As you have correctly pointed out

$$T^{00} = (e + p)u^{0}u^{0} - p = e,$$

where you have correctly shown $u^{0}u^{0} = 1$.

Now, the mistake comes from the way you have derived the four-velocity from the expression for the metric. The correct way to derive the four-velocity here is to first write the four-velocity as

$$u^{\alpha} = \frac{\mathrm{d}}{\mathrm{d}\tau}(x^{0}, x^{i})^{\mathsf{T}},$$

which gives

$$u^{0} = \frac{\mathrm{d}t}{\mathrm{d}\tau} = \gamma.$$

Then of course, in the fluid rest frame we get $(u^{0})^{2} = 1$ as before.

I hope this helps.


Edit. To address your comments:

For a particle with fixed spatial coordinates $x^{i}$, the interval elapsed as it moves forward in time is negative, $\mathrm{d}s^{2} = −\mathrm{d}t^{2} < 0$. This leads us to define the proper time via

$$\mathrm{d}\tau^{2} = -\mathrm{d}s^{2}.$$

The proper time elapsed along a trajectory through space-time will be the actual time measured by an observer on that trajectory. Some other observer, as we know, will measure a different time.

A path through space-time is specified by giving the four space-time coordinates as a function of some parameter, $x^{\mu}(\lambda)$, where typically for time-like paths the most convenient parameter to use is the proper time $\tau$. So we can write

$$\tau = \int \sqrt{-\mathrm{d}s^{2}} = \int \sqrt{-g_{\mu\nu}\frac{\mathrm{d}x^{\mu}}{\mathrm{d}\tau}\frac{\mathrm{d}x^{\nu}}{\mathrm{d}\tau}}\mathrm{d}\tau,$$

The tangent vectors $u^{\mu} = \mathrm{d}x^{\mu}/\mathrm{d}\tau$, are our four-velocities and these can be automatically normalised so we have

$$g_{\mu\nu}u^{\mu}u^{\nu} = u_{\mu}u^{\nu} = -1.$$

To convince your self of this you can consider the above expression in the fluid rest frame. Here, we have $\gamma = 1$ and $u^{i} = 0^{i}$. Thus, $u^{\mu} = (1, u^{i})^{\mathsf{T}}$. Now, again considering the rest frame of the fluid, we can clearly see

$$u^{0}u^{0} = 1.$$

Again, I hope this helps.

share|improve this answer
    
In your notations can you define what is $\tau$ in my notations (as a function of $s$ or/and $t$) –  Vincent May 5 '13 at 15:01
    
$\tau$ is the proper-time. Time measured in the rest frame of the fluid. It is defined as $\mathrm{d}\tau^{2} = \mathrm{d}S^{2}/c^{2}$. –  Killercam May 5 '13 at 15:07
    
Thanks. And what is the notation $(x^0, x^i)^T$ ? –  Vincent May 5 '13 at 15:08
1  
The four-velocity as I have written it is contravariant. Contravaient vectors are usually written as column vectors. So, to make a vector represented by a row $(x, y, z)$ represent a contravariant/column vector, we take the transpose. This is very pedantic on my part, but something I always like to do when writing vectors in this way. For more about Covariance and contravariance see Wikipedia. –  Killercam May 5 '13 at 15:35
    
Oh, ok, I do not see this as pedantic but completely justified. But I still do not understand from where comes the minus between $\frac{dx^0}{d\tau}$ and $-\frac{dt}{d\tau}$ because for me $x^0=t$ (so when I write $g_{00}dx^{0}dx^{0}$ I get $-c^2dt^2$). –  Vincent May 5 '13 at 15:44

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.